Pollen Biology of Grewia optiva Drummond Genotypes: An Important Agroforestry Tree of North Western Himalayas - N.V., Saresh; Verma, Archana; Godara, Asu Singh; Meena, Dharmendera; Bijarnia, Arjun Lal (Annals of Arid Zone, 2022)
Grewia optiva is an important agroforestry tree of Himalayas because of its utility as fodder, fuel and fibre. Therefore, for breeding and conservation of the species the study of the components of pollen biology is important. In the present investigation it was observed that pollen grains of Grewia optiva were isopolar radio symmetric normal and fertile and size ranges from 49.00 to 74.37 μ. Positive correlation was observed among anther and flower levels (0.985), anther number and pollen, production per anther (0.686) and anther number and pollen production per flower (0.800). Pollen viability rates significantly differed among freshly collected pollen grains and stored pollen grains at 4oC and -20°C. The percentage of fruit set were found to decrease with the collection time of pollen grains, at the beginning of anther dehiscence it was 68-79%, after 6 h 39-53% and 24 h of anthesis 26-38%. The present experiment showed that 20% sucrose with BKM (Brewbaker and Kwack’s medium) was the optimum medium for the germination of pollen grains. Germination percentage was maximum in genotype BI-4 (20.40%) and minimum in SO-3 (5.20%). The stigma became receptive 14-20 hours after pollination and the species is found to be self-compatible. The variation in size, pollen production, viability and germination per cent was because of genetic differences among the genotypes and external factors like temperature, humidity etc. The findings provide important insight to understand the reproductive biology of G. optiva and to develop planned breeding programme for the species.